Exploring the influence of video on staff attributions and perceptions regarding challenging behaviour: an innovative approach to group consultation - Hussain, Sofia N. (2016)
Exclusion rates for challenging pupil behaviour (CB) are increasing (DfE; SFR-28/2015). Where staff attribute CB to within-child or home-related factors, low perceived self-efficacy, negative attitudes and exclusionary practice amongst staff may increase (Jager & Denessen, 2015). Group problem-solving approaches including Circles of Adults (CoA) aim to facilitate staff attributions. Given their equivocal influence, such approaches require attunement and systematic research (Gulliford, 2015). Based on educational research (Gaudin & Chaliès, 2015), this study explored the impact of video-data within CoA via a mixed method, pre-post-test experimental, cluster randomisation design where staff reviewed video-data (experimental n=20) or, written-data (comparison n=19).